The feasibility of using circular training method for skiers-junior with regard typological properties nervous system - V. I. Omelyanenko (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: to determine the effect of a circular method of training on physical performance junior skiers depending on the strength of the nervous system. Material : the study involved 22 skiers (age 11 years). They were divided into 2 groups (11 people): experimental and control. In the experimental group 1 weekly circular training method used. The study was conducted in consultation with parents. Performance was determined using a bicycle ergometer first baseline and at 6 months after the study. At one stage (preparatory) conducted screening test and familiarize coaches with the goals and objectives of the study. Stage 2 (experimental): a) the subjects were divided into 2 groups; b) determined hypnotizability subjects; c) performance evaluation test was conducted at the beginning and end of the study. At stage 3 (final) analyzed the results of the study. Results : It was found that all subjects grade 3 hypnotic state. In the experimental group (using group training) after 6 months of regular exercise saw an increase in physical performance by an average of 56 kg m / min. In the control group (training was accepted by the program) there was an increase in physical performance average of 52 kg m / min. Conclusions: noted that all skiers same strength nervous system (weak). It is recommended to conduct training on the same program. Circuit Training should be carried out taking into account the anthropometric data and the initial physical fitness. Circular method of training does not contradict the basic principles of skiers: a gradual increase in the volume and intensity of physical activity.